A Blockchain Microsites-Based Ecosystem for Learning and Inclusion - Martins, Valéria Farinazzo; Oyelere, Solomon Sunday; Tomczyk, Łukasz; Barros, Gabriel; Akyar, Özgür Yaşar; Eliseo, Maria Amelia; Amato, Cibelle Albuquerque de La Higuera; Silveira, Ismar Frango (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2019.229, 2019)
Several initiatives have made available open educational resources, offered through educational platforms, aiming to achieve a broader audience, thus having the opportunity of democratizing knowledge. However, accessibility aspects in these resources still have many gaps. One is how to help teachers to prepare curricular contents available to all students, regardless of their limitations and disabilities. In this sense, this paper presents a digital ecosystem architecture, called SELI, that is being developed by a group of eleven European and Latin American countries. This ecosystem aims to provide an accessible learning environment and its contents, besides proper authoring tools based on recent technologies such as Blockchain, microsites, and universal accessibility guidelines.